VD_FINDINFO AP / 2012 / 4 vom 30. November 2011 - VD Tribunal cantonal (2011)
DÉCISION INCIDENTE, APPEL EN CAUSE, PRESCRIPTION, ACTION EN DOMMAGES-INTÉRÊTSEN GÉNÉRAL, DÉFAUT DE LA CHOSE | 127 CO, 135 CO, 143 CO, 259e CO, 50 CO, 51 CO, 452 al. 1 CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 83 CPC, 84 al. 3 CPC, 404 al. 1 CPC (CH)